Assessment of ecological values of greening landscape elements in the Great Hungarian Plain - Máté, Klaudia (Journal of Environmental Geography, 2017)
The research examines the effects of agricultural subsidies on the landscape structure. According to the hypothesis, greening – which has been introduced as part of the European Union’s Common Agriculture Policy (EU CAP) reform –, if it is properly controlled and applied, can be a suitable tool for habitat network development. Landscape elements eligible for greening can function as significant landscape structural elements, and can promote the achievement of goals e.g. in the preservation of biodiversity. As part of this research, field surveys were performed in 2016 and 2017 in the Great Hungarian Plain, where significant landscape elements were assessed and documented in the sample area. During the research, Shape Index and Fractal Dimension Index values for polygonal elements were calculated based on their current extensions in 2016 and in 2017. In line with my basic hypothesis, eligible landscape elements (such as hedgerows, stonewalls, shadoofs and infield trees) do not possess extraordinary ecological values, nor can their persistence be guaranteed solely with greening subsidies. Therefore, they may also not be able to fill their role in the protection of landscape structure and biodiversity in the long term.